The relationship between graduate employability and employers’ decision to hire - Nur Hidavah, Mohammad (Universiti Malaysia Sarawak (UNIMAS), 2019)
This study is aimed at exploring the relationship between graduate employability and employers' decision to hire. This study was conducted based on USEM model proposed by Knight & Yorke (2004) and it was rebelling by Pool & Swell (2007) stated that USEM model is largely theoretical and lacks research evidence. Thus, researcher conducted this study to prove the relevance of the USEM model in explaining the graduate employability. The results show there is a significant relationship between the independent variable (understanding, skills, efficacy-belief and metacognition) and dependent variable (employers' decision to hire). Quantitative research methodology used in this research and the data was collected using questionnaire as the instrument with 100 respondents participate from manufacturing companies. The criterion sampling was used in this research as the title of the research is more about employer's perspective and their decision to hire based on several factors. Pearson correlation and Spearman correlation were used to measure the relationship between factors influence graduate employability and employers' decision to hire. While multiple regression was used to determine the dominant factors contribute to the employers' decision to hire. As such, researcher recommend a focus employability on graduate itself, Higher Education and employer.